English and Nepali Nouns through the Lens of Componential Analysis - Nabaraj Neupane, (Kaumodaki: Journal of Multidisciplinary Studies, 2025)
The meanings of nouns are crucial in facilitating cross-linguistic communication, which is increasingly common in the multilingual world. This article examines English and Nepali nouns using the theory of componential analysis, which analyzes the meanings of words as combinations of universal semantic components. To achieve the objective, this study adopted the document analysis method. The important semantic features of English and Nepali nouns were identified by exploring sources like Ekta English-Nepali Dictionary (1st ed.) and Oxford Advanced Learner’s Dictionary (10th ed.). First, equivalence was found in gender, such as cock: hen: chick:: bhāle: pothi: callā. Second, semantic overlap was noticed between the English nouns ‘leather’, ‘skin’, and ‘shell’, and the Nepali nouns chālā, bokrā, and khostā. Finally, some meanings of nouns were found converged while others diverged. For instance, Nepali terms like kākā (father’s brother) and māmā (mother’s brother) converge to mean ‘uncle’ in English, while ‘nephew’ diverges into Nepali terms like bhatijā (brother’s son) and bhanjā (sister’s son). These findings are significant for lexicographers, semanticists, and material developers in creating suitable resources. They also help second language teachers to reduce learners’ errors and choose effective vocabulary teaching strategies.